-3(x-2)m=6-3x

Simple and best practice solution for -3(x-2)m=6-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-2)m=6-3x equation:


Simplifying
-3(x + -2) * m = 6 + -3x

Reorder the terms:
-3(-2 + x) * m = 6 + -3x

Reorder the terms for easier multiplication:
-3m(-2 + x) = 6 + -3x
(-2 * -3m + x * -3m) = 6 + -3x
(6m + -3mx) = 6 + -3x

Solving
6m + -3mx = 6 + -3x

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Reorder the terms:
-6 + 6m + -3mx + 3x = 6 + -3x + -6 + 3x

Reorder the terms:
-6 + 6m + -3mx + 3x = 6 + -6 + -3x + 3x

Combine like terms: 6 + -6 = 0
-6 + 6m + -3mx + 3x = 0 + -3x + 3x
-6 + 6m + -3mx + 3x = -3x + 3x

Combine like terms: -3x + 3x = 0
-6 + 6m + -3mx + 3x = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(-2 + 2m + -1mx + x) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-2 + 2m + -1mx + x)' equal to zero and attempt to solve: Simplifying -2 + 2m + -1mx + x = 0 Solving -2 + 2m + -1mx + x = 0 Move all terms containing m to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2m + -1mx + 2 + x = 0 + 2 Reorder the terms: -2 + 2 + 2m + -1mx + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2m + -1mx + x = 0 + 2 2m + -1mx + x = 0 + 2 Combine like terms: 0 + 2 = 2 2m + -1mx + x = 2 Add '-1x' to each side of the equation. 2m + -1mx + x + -1x = 2 + -1x Combine like terms: x + -1x = 0 2m + -1mx + 0 = 2 + -1x 2m + -1mx = 2 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4a-1=3 | | (9+2x)3=4+13 | | 5x+7=9x-5 | | -3/5t=-12 | | 5-1/4 | | (8x+1)/2=(t+8)/4+(t-6)/4 | | 8+2x(4)=x(3)+7 | | -5(t+1)-t-14=-6(t+5)+11 | | 6(2x-2)=126 | | 8x+1/2=t+8/4+t-6/4 | | 6.28*9=x | | 65=2x-7 | | 8+2x(4)=3x+7 | | 2(x-2)=3(x-9) | | 625x+1500=4000 | | y+15=6y-45 | | 2x+1=8x-53 | | 7(3+6)=11-(x+2) | | 8.25+x=22.5 | | 0.05x+0.50(100-x)=-0.35x | | n+2.3=1.25 | | p+p+11+4p-33=752 | | 9x-1=6+8x | | -27+n=-51 | | -2x=12-4 | | 16.8-x=6x | | x+1=7-x | | 3.25-5=5-1.8s | | y-15=6y-45 | | x^2+4x=30 | | 2y+4x=8fory | | 3.5/x=-0.2 |

Equations solver categories